Amyotrophic Lateral Sclerosis Is Associated with Hypolipidemia at the Presymptomatic Stage in Mice - Kim, Sung-Min (Public Library of Science, 2011)
OBJECTIVE: To demonstrate that hypolipidemia is a typical feature of the mouse model of amyotrophic lateral sclerosis (ALS) and to assess the association between hypolipidemia and disease stage, dietary intake, and sex. METHODS: We compared daily dietary intake, body weight, and serumlipid and glucose levels in ALS mice and wild-type controls at different stages of the disease. FINDINGS: Total cholesterol low-density lipoprotein (LDL) and LDL/high-density lipoprotein (HDL) ratio were significantly lower in ALS mice compared with controls. Subgroup analysis revealed that the incidence of hypolipidemia was significantly greater in male, but not female, ALS mice compared with control mice and that hypolipidemia was present at the presymptomatic stage of the disease. This hypolipidemia can be found without a decrease in the serum levels of other energy sources, such as glucose, in the presymptomatic stage. CONCLUSIONS: Hypolipidemia is present at the presymptomatic stage of the ALS mouse model in the absence of malnutrition, significant neuromuscular degeneration or regeneration, and respiratory difficulty. Our findings suggest that hypolipidemia might be associated with the pathomechanism of ALS and/or lipid-specific metabolism rather than simply an epiphenomenon of neuromuscular degeneration or energy imbalance.